2005
DOI: 10.1038/sj.bmt.1704996
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal follow-up of body composition in hematopoietic stem cell transplant patients

Abstract: Summary:Patients with hematological malignancies are well nourished prior to allogeneic hematopoietic stem cell transplantation (HSCT). HSCT and associated complications can affect body composition. The study evaluated crosssectionally the prevalence and longitudinally the changes in lean body mass index (LBMI) in HSCT patients. Patients (n ¼ 82) were classified as normal or low LBMI. Logistic regression analyses were used to estimate odds ratios (OR) for low vs normal LBMI, between healthy volunteers and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 34 publications
4
54
0
3
Order By: Relevance
“…Loss of fat may be temporary. Results on adult 32 and paediatric 33 PBSC transplantation survivors (both ⩾ 4-6 years survival), and breast cancer survivors (⩾6 months survival) 34 showed weight recovery favoured fat gain over LBM. This trend of change is not desirable as excess FM can mask a LBM deficit, as well as increase the risks of overweight-related health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of fat may be temporary. Results on adult 32 and paediatric 33 PBSC transplantation survivors (both ⩾ 4-6 years survival), and breast cancer survivors (⩾6 months survival) 34 showed weight recovery favoured fat gain over LBM. This trend of change is not desirable as excess FM can mask a LBM deficit, as well as increase the risks of overweight-related health issues.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Moreover, Lenssen et al 9 reported Course of nutritional status in alloHCT P Urbain et al that the frequency of depleted muscle reserves rose independently of weight changes during the first post-transplant year in alloHCT recipients. Kyle et al 11 even showed that any loss of weight and lean body mass experienced during the immediate post-transplant period (reflecting muscle mass among other factors) is not regained during the first year. Possible explanatory models include among others decline in physical activities for up to 1 year after transplantation, 9 a negative energy balance due to hypermetabolism, and the catabolic effects on skeletal muscle exerted by medication with corticosteroids 5,6 as well as immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] To date, few studies have assessed nutritional status before alloHCT, and most of them only recorded body mass index (BMI) as a potential risk factor for survival. [7][8][9][10] Except for one report by Kyle et al 11 on the development of lean body mass, there were until now no longitudinal data on nutritional status and body composition in the early post-transplant period, although several reports showed that depletion of micronutrients, mainly vitamin D, is common before and after alloHCT. [12][13][14] There are now many nutritional parameters available and validated for cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In particular patients with chronic (c)GVHD had a significantly lower LBM index, and steroid treatment was associated with a lower LBM index and a higher body fat mass index. 12 In a small prospective study (n ¼ 47 patients who underwent allo-SCT), around 50% of patients experienced diarrhoea at median of 10 days after allo-SCT; diarrhoea had a profound negative effect on nutritional status and well-being, despite the administration of TPN in the majority of those patients. 11 A few studies investigated nutritional status in patients with GVHD, and looked at differences between subgroups with limited and extensive (or active and inactive) GVHD.…”
Section: Results Of the Literature Studymentioning
confidence: 99%
“…11,12 A large prospective study of high quality showed allo-SCT patients had a lower LBM index than healthy controls, at 6 and 12 months up to 6 years post transplant. In particular patients with chronic (c)GVHD had a significantly lower LBM index, and steroid treatment was associated with a lower LBM index and a higher body fat mass index.…”
Section: Results Of the Literature Studymentioning
confidence: 99%